Trust model based on reputation for peer-to-peer networks - TIAN Chun-qi1; ZOU Shi-hong2; WANG Wen-dong2; CHENG Shi-duan2 (Tongxin xuebao)
A novel trust model for P2P networks was proposed,in which the trust value of a given peer was computed using its local trust information and recommendation from other nodes. A generic method for quantifying and updating the credibility of a recommender was also put forward. With regard to risk element,the risk was quantified by informa-tion entropy and so trust degree and uncertainty degree was presented in uniform form. Subsequent experimental results show that,compared to some trust models,the proposed model is more robust on trust security problems and more ad-vanced in successful transaction rate. So the trust model can perform much better especially in helping peers establish trust relationships in open P2P networks.